KOMUNIKASI PEMBANGUNAN DALAM MENDORONG KEMANDIRIAN WARGA BANGKIT DARI SITUASI PASCABENCANA MELALUI PERTANIAN: Studi Kasus Komunitas Rahmat Tani, Desa Ombo Sirenja, Kabupaten Donggala, Sulawesi Tengah - Santi Praharsiwi, Caecilia (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2022)
The dynamics of communication that occur in society to recover from disaster situations is an important study. Awareness of the situation and the independence of citizens to find solutions will be the key to the success of sustainable development. Through a case study in the Rahmat Tani community in Ombo Sirenja Village, Donggala District, Central Sulawesi, this research focuses on the dynamics of communication when post-disaster development ideas are actually born from the community. The community here is seen as a subject trying to recover from a post-disaster situation, and rebuild economic stability after the disaster situation is over. Therefore, the main theoretical study in this study is the theory of the role of communication in development in society (communication for development) or also known as communication for social change (SCS) which implements participatory communication by farming communities. Participatory communication exists as a way to support development in society by applying the principles of equality and openness to all parties involved. As a result, the Rahmat Tani community was formed from a shared awareness that presents solutions to increase economic independence for the people in their village.